Beneficial Effects of Ursodeoxycholic Acid on Metabolic Parameters and Oxidative Stress in Patients with Type 2 Diabetes Mellitus: A Randomized Double-Blind, Placebo-Controlled Clinical Study - Lakić, Biljana; Škrbić, Ranko; Uletilović, Snežana; Mandić-Kovačević, Nebojša; Grabež, Milkica; Šarić, Mirna Popović; Stojiljković, Miloš P.; Soldatović, Ivan; Janjetović, Zorica; Stokanović, Anastasija; Stojaković, Nataša; Mikov, Momir (Journal of Diabetes Research, 2024)
Background. Oxidative stress and inflammation are closely related pathophysiological processes, both occurring in type 2 diabetes mellitus (T2DM). In addition to the standard treatment of T2DM, a potential strategy has been focused on the use of bile acids (BAs) as an additional treatment. Ursodeoxycholic acid (UDCA), as the first BA used in humans, improves glucose and lipid metabolism and attenuates oxidative stress. The aim of this study was to evaluate the potential metabolic, anti-inflammatory, and antioxidative effects of UDCA in patients with T2DM. Methods. This prospective, double-blind, placebo-controlled clinical study included 60 patients with T2DM, randomly allocated to receive UDCA or placebo. Subjects were treated with 500 mg tablets of UDCA or placebo administered three times per day (total dose of 1500 mg/day) for eight weeks. Two study visits, at the beginning (F0) and at the end (F1) of the study, included the interview, anthropometric and clinical measurements, and biochemical analyses. Results. UDCA treatment showed a significant reduction in body mass index (p=0.024) and in diastolic blood pressure (p=0.033), compared to placebo. In addition, there was a statistically significant difference in waist circumference in the UDCA group before and after treatment (p<0.05). Although no statistical significance was observed at the two-month follow-up assessment, an average decrease in glucose levels in the UDCA group was observed. After two months of the intervention period, a significant decrease in the activity of liver enzymes was noticed. Furthermore, a significant reduction in prooxidative parameters (TBARS, NO2-, H2O2) and significant elevation in antioxidative parameters such as SOD and GSH were found (p<0.001). Conclusions. The eight-week UDCA administration showed beneficial effects on metabolic and oxidative stress parameters in patients with T2DM. Thus, UDCA could attenuate the progression and complications of diabetes and should be considered as an adjuvant to other diabetes treatment modalities. This trial is registered with NCT05416580.